2013
DOI: 10.2478/10004-1254-64-2013-2428
|View full text |Cite
|
Sign up to set email alerts
|

Oxalate: From the Environment to Kidney Stones

Abstract: Oxalate urolithiasis (nephrolithiasis) is the most frequent type of kidney stone disease. Epidemiological research has shown that urolithiasis is approximately twice as common in men as in women, but the underlying mechanism of this sex-related prevalence is unclear. Oxalate in the organism partially originate from food (exogenous oxalate) and largely as a metabolic end-product from numerous precursors generated mainly in the liver (endogenous oxalate). Oxalate concentrations in plasma and urine can be modifi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 184 publications
(227 reference statements)
2
52
0
5
Order By: Relevance
“…Accumulating lines of evidence suggest that renal tubular cell injury and fixed crystal particles could be implicated in the pathogenesis of urolithiasis [2][4]. Others have postulated that excessive excretion of urinary oxalate could cause substantial damage to the renal epithelium [5].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating lines of evidence suggest that renal tubular cell injury and fixed crystal particles could be implicated in the pathogenesis of urolithiasis [2][4]. Others have postulated that excessive excretion of urinary oxalate could cause substantial damage to the renal epithelium [5].…”
Section: Introductionmentioning
confidence: 99%
“…Endogenous oxalate production is thought to be fairly constant, attributing for up to 60–80% of total plasma oxalate and urinary oxalate excretion [6, 7]. Oxalate biosynthesis evolves from glyoxylate [8, 9, 10, 11] as central precursor molecule.…”
Section: Oxalate – Endogenous Productionmentioning
confidence: 99%
“…Total daily oxalate excretion by the kidney is estimated at 10–40 mg per 24 h (0.1–0.45 mmol per 24 h) in healthy children and adults, with the average excretion being slightly higher in males than in females [34, 37, 56, 57, 58]. Only a minor part is eliminated through the gastrointestinal tract [6]. Marengo et al reported fecal oxalate excretion to account for only 5–7% of the oxalate administered in rats treated with subcutaneously implanted minipumps [37].…”
Section: Hyperoxaluria – Disturbed Oxalate Homeostasismentioning
confidence: 99%
“…Uważa się, że jednym z podstawowych czynników sprzyjających powstawaniu szczawianów i odkładaniu się złogów są stany zapalne [3,5]. Istotne znaczenie ma także nadmierne zagęszczenie wydalanych związków na skutek ograniczenia objętości moczu [6].…”
Section: Kamica Szczawianowaunclassified